2020
DOI: 10.1200/jco.2020.38.6_suppl.438
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized placebo-controlled neoadjuvant trial of nintedanib or placebo with gemcitabine and cisplatin in locally advanced muscle invasive bladder cancer (NEO-BLADE).

Abstract: 438 Background: Neo-adjuvant chemotherapy Improves overall survival in patients with MIBC. Nintedanib is an orally available, potent, small molecule, triple kinase inhibitor with the potential to further benefit patient prognosis. Methods: NEO-BLADE was designed as a randomised, placebo controlled phase II study (n=120) to compare the addition of nintedanib (N) (150mg/200mg BD) to a combination of Gemcitabine (G) and Cisplatin (C). The study was powered (80%, alpha=15% [one sided]) to detect an improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The promising results in early chemoimmunotherapy trials have led to three phase 3 trials testing Nivolumab (ENERGIZE; NCT03661320), Durvalumab (NIAGARA; NCT03732677) Pembrolizumab (KEYNOTE-866; NCT03924856) in cisplatin eligible and one trial testing Pembrolizumab (KEYNOTE-905; NCT03924895) in cisplatin ineligible patients respectively. Similarly, adding Nintedanib, a triple receptor tyrosine kinase inhibitor targeting VEGFR 1-3, FGFR 1-3, and PDGFR α and β to GC showed that while there was no significant difference in pathologic responses, both 12-months and 24-months PFS and OS were significantly improved with addition of angiogenesis inhibition [30].…”
Section: Intensifying Neoadjuvant Treatmentmentioning
confidence: 99%
“…The promising results in early chemoimmunotherapy trials have led to three phase 3 trials testing Nivolumab (ENERGIZE; NCT03661320), Durvalumab (NIAGARA; NCT03732677) Pembrolizumab (KEYNOTE-866; NCT03924856) in cisplatin eligible and one trial testing Pembrolizumab (KEYNOTE-905; NCT03924895) in cisplatin ineligible patients respectively. Similarly, adding Nintedanib, a triple receptor tyrosine kinase inhibitor targeting VEGFR 1-3, FGFR 1-3, and PDGFR α and β to GC showed that while there was no significant difference in pathologic responses, both 12-months and 24-months PFS and OS were significantly improved with addition of angiogenesis inhibition [30].…”
Section: Intensifying Neoadjuvant Treatmentmentioning
confidence: 99%
“…Combination strategies with targeted therapies are also being investigated. Phase II results have been reported from durvalumab plus olaparib (NEO-DURVARIB trial) and nintedanib, a tyrosine kinase inhibitor, plus GC (NEO-BLADE trial), with pCR rates 50% and 37% respectively [275,276]. The NEO-BLADE trial also reported improved OS over GC alone with HR 0.38, p = 0.018.…”
Section: Immune Checkpoint Inhibitors (Cpis) and Targeted Therapiesmentioning
confidence: 99%